Exploring the Knowledge Gaps of Crowdfunding Firms: A Survey of Crowdfunding Firms and Auditors - Aland, John (Journal of Accounting and Finance, 2022)
Prior research shows that the accounting and financial reporting quality of startups and early-stage firms is lower than that of public firms and firms later in their life-cycle. A growing source of financing for these startup and early-stage firms is equity crowdfunding. This paper provides evidence, through survey responses and semi-structured interviews with a subset of respondents, about “knowledge gaps” and accounting “weak spots” that exist for firms raising capital through Regulation Crowdfunding. “Knowledge gaps” are accounting areas where startup companies think they understand the proper accounting for these items, while auditors say these firms struggle with these concepts. Accounting “weak spots” are accounting areas where startup firms and auditors agree there is difficulty in accounting for certain items, and where more guidance or clearer standards may be beneficial. Better understanding specific accounting “knowledge gaps” and “weak spots” can help inform these startup firms, their auditors, their investors, and their regulators when evaluating and considering the reported financial condition of these companies.